Integration requirements for immigrants in europe : a legal-philosophical inquiry - De waal, tamar (London [England] : HART PUBLISHING, 2021)
"Based on legal-philosophical research informed by insights gleaned from empirical case studies, this book sets out three central claims about integration requirements as conditions for attaining increased rights (ie family migration, permanent residency and citizenship) in Europe: (1) That the recent proliferation of these (mandatory) integration requirements is rooted in a shift towards 'individualised' conceptions of integration. (2) That this shift is, on the one side, counterproductive as it puts barriers to participation and inclusion of newcomers (who will most likely permanently settle) and on the other, normatively problematic, insofar as it produces status hierarchies between native-born and immigrant citizens. (3) That the remedy for this situation is a firewall that disconnects integration policy from access to rights. The book draws on perspectives on immigrant integration in multiple EU Member States and includes legal and political reactions to the refugee/migrant crisis."--
List of Abbreviations -- Introduction -- 1. Methodological Considerations -- 2. Academic Relevance and Contribution to the Literature -- 3. Preliminary Remarks -- 4. Outline of the Book -- 1. From Societal to Individual Integration -- 1. The Growth of Integration Requirements in Multiple EU Member States -- 1.1. Family Reunification -- 1.2. Obtaining Permanent Residency -- 1.3. Naturalisation -- 2. Integration: Old en New -- 2.1. Integration as a Condition of Society -- 2.2. Integration as a Condition of Individuals -- 2.3. Individualised Integration and Integration Requirements in Europe: Exploring the Links -- 2.4. Conclusion -- 2. Structural Risks of Integration Requirements -- 1. Liberal Nationalism and Social Sciences on Integration Requirements -- 2. Integration Policies in Principle or Reality -- 3. The Politics of Integration Requirements -- 4. Individualised and Contractualised Integration -- 4.1. Individualised Integration -- 4.2. The Contractualisation of Secure Residency and Citizenship -- 5. Conclusion -- 3. Integration within a Community of Equals -- 1. Social Equality and Justice -- 2. Migration, Equal Citizenship and Social Inequalities -- 2.1. Importance of Naturalisation -- 2.2. Stigmatisation of (Those Who Become) Citizens -- 3. Integration Requirements: To Deserve to be One of 'Us' -- 3.1. Unwanted Citizens -- 3.2. Conditional Belonging -- 4. Universal Values and Equal Citizenship -- 5. The Other Side of the Coin: Denaturalisation -- 6. Conclusion -- 4. Disconnected Integration from Rights -- 1. Problems with the Current Integration Requirements in European Member States -- 1.1 Abuse of Precarity -- 1.2 Decreased Naturalisation Rates -- 1.3 Inculcating Hierarchies in Citizenship -- 1.4 Ineffective Integration Strategies -- 2. The Firewall Solution -- 3. The Problem-Solving Capacity of Disconnecting Rights from Integration Strategies -- 3.1. Counterbalancing Precarity -- 3.2. Enabling Naturalisation -- 3.3. Counterbalancing Conditional Belonging -- -- 3.4. Avoiding Ineffective Integration Strategies -- 4. More Innovative Integration Strategies -- 4.1 Customised Integration Approaches -- 4.2 Other Migrant Groups -- 4.3 Trajectories for Asylum Seekers -- 5. Possible Counterarguments Against the Firewall -- 5.1. Limitations of Public Spending -- 5.2. Enforcing Integration -- 5.3. The Ritual of Becoming a Citizen -- 5.4. Having the Competency to Vote Conclusion -- 1. Conclusions -- 2. Future Research.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Jurisprudence & philosophy of law; Electronic books